Millennial Generation and Smartphone Purchase Intention - Yuli Asbar; Sapna Biby; Razif Razif; Widyana Verawaty Siregar (Management Research and Behavior Journal, 2021)
Smartphones are the most popular in use among the younger generation, with 81% of young people having their own phones. Smartphone technology, with its high functionality, certainly change the behavior of people, especially young adults as the frequent use of smartphones at this time. From the findings of young adult behavior change and the increasingly competitive issues between brands of smartphones, this research will identify the intentions of purchasing their smartphones. From the results of the above research can be concluded that the purchase of consumer influenced by brand image. The higher status of brand image, the more purchase intentions there are. The correlation between product knowledge and purchase intentions is known that consumer purchase intentions are influenced by the amount of product knowledge. Perceived of price as a moderator, from the statistical results can be concluded that when consumers buy better (high) on the suitability of prices to the products with higher brand image. Meanwhile, price conformity does not contribute to the correlation between product knowledge and buyer intentions.